Corruption, Tax Evasion and the Laffer Curve - Ira N. Gang; Amal Sanyal; Omkar Goswami (Rutgers University, Department of Economics, 1998)
We introduce bureaucratic corruption in a simple way and examine its effect on government revenue when policies change. We show that a rise in the tax rate can lead to a fall in net revenue–a Laffer curve result due to the proportion of auditors that are corrupt and enforcement costs. It may pay for the government to lower audit probabilities and induce cheating. If corruption is low enough, revenues garnered from capturing people cheating may exceed those from choosing an audit structure in which everyone declares their true income. We also examine a case in which corruption is endogenous.
Keywords: D73; H26; O23; 330; auditing; bureaucracy; corruption; laffer curve; tax evasion